=2(a+3)+3(2a-1)

Simple and best practice solution for =2(a+3)+3(2a-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for =2(a+3)+3(2a-1) equation:


Simplifying
0 = 2(a + 3) + 3(2a + -1)

Reorder the terms:
0 = 2(3 + a) + 3(2a + -1)
0 = (3 * 2 + a * 2) + 3(2a + -1)
0 = (6 + 2a) + 3(2a + -1)

Reorder the terms:
0 = 6 + 2a + 3(-1 + 2a)
0 = 6 + 2a + (-1 * 3 + 2a * 3)
0 = 6 + 2a + (-3 + 6a)

Reorder the terms:
0 = 6 + -3 + 2a + 6a

Combine like terms: 6 + -3 = 3
0 = 3 + 2a + 6a

Combine like terms: 2a + 6a = 8a
0 = 3 + 8a

Solving
0 = 3 + 8a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-8a' to each side of the equation.
0 + -8a = 3 + 8a + -8a
Remove the zero:
-8a = 3 + 8a + -8a

Combine like terms: 8a + -8a = 0
-8a = 3 + 0
-8a = 3

Divide each side by '-8'.
a = -0.375

Simplifying
a = -0.375

See similar equations:

| 1.5(x-6)=-6 | | 2h=-12 | | x+0.03x=3000 | | 80-3x=5x+9 | | 6x-11=-2x+13 | | (24+8x+7y)-(4x+6y+56)=0 | | (7x-12)=(6y+8) | | 3t-2=10 | | 20r+15=365 | | (7x-12)-(-2x+3)= | | X^2+10x+C=-5+c | | 2500-40.5x=-3000 | | x-8=x-36 | | 15p+5=95 | | 9k+30=120 | | 10p+1=81 | | 2c+2=16 | | -2500-40.5x=-3000 | | 12+(-2)+7+4+(-6)= | | a=q^2+13q+23 | | 4y-2+y+29=6y+30-4y | | x-10=x-10 | | 7x+7x=48 | | (3x-15)-(-7x+4)= | | (2x+1)(2x)= | | 7(-3x+5)-1+-2-15x= | | 9(t^2)-6t+50=0 | | 5x+14=-14-9 | | -5y+8=-7 | | 8+2x-4=9x+7-4x | | N-5-7n=19 | | 0=15x+10 |

Equations solver categories